Structural and spectroscopic characterization of a new series of Ba2RE2Ge4O13 (RE = Pr, Nd, Gd, and Dy) and Ba2Gd2−xEuxGe4O13 tetragermanates. Issue 31 (27th July 2021) - Lipina, Olga A.; Surat, Ludmila L.; Chufarov, Alexander Yu.; Tyutyunnik, Alexander P.; Enyashin, Andrey N.; Baklanova, Yana V.; Chvanova, Anastasia V.; Mironov, Leonid Yu.; Belova, Ksenia G.; Zubkov, Vladimir G.
Abstract : A new series of Ba2 RE2 Ge4 O13 and Ba2 Gd2− x Eu x Ge4 O13 tetragermanates crystallizing in the monoclinic system (S.G. C 2/ c ) have been characterized by various methods. The studied Ba2 Gd2− x Eu x Ge4 O13 phosphors are appropriate for applications in UV-excited pc-LEDs. Abstract : A new series of Ba2 RE2 Ge4 O13 (RE = Pr, Nd, Gd, Dy) germanates and Ba2 Gd2− x Eu x Ge4 O13 ( x = 0.1–0.8) solid solutions have been synthesized using the solid-state reaction technique and characterized by X-ray powder diffraction. All compounds crystallize in the monoclinic system, space group C 2/ c, Z = 4. The crystal lattice consists of RE2 O12 dimers, zigzag C 2 -symmetric [Ge4 O13 ] 10− tetramers, and ten-coordinated Ba atoms located in voids between polyhedra. The density-functional theory (DFT) calculations performed on a rich set of Ba2 RE2 Ge4 O13 compounds have confirmed the high thermodynamic stability of monoclinic modification. Under ultraviolet (UV) light excitation Ba2 Gd2− x Eu x Ge4 O13 phosphors exhibit an orange-red emission corresponding to the characteristic f–f transitions in Eu 3+ ions. The highest intensity of lines at 580 nm ( 5 D0 → 7 F0 ), 582–602 nm ( 5 D0 → 7 F1 ), 602–640 nm ( 5 D0 → 7 F2 ), 648–660 nm ( 5 D0 → 7 F3 ), and 680–715 nm ( 5 D0 → 7 F4 ) is observed for the samples with x = 0.4–0.6. The possibility of their application has been assessed by studying their color characteristics, quantum efficiency, and thermal stability. The obtained data indicate that Ba2 Gd2− x Eu x Ge4 O13 solids can be considered as promising materials for UV-excited phosphor-converted light-emitting diodes (LEDs) if an aluminum nitride substrate ( λ ex = 255 nm) is used as a semiconductor chip.